Introduction: Empirical Research on Decision-Making in the Federal Courts - Andrew D. Martin (Washington University Journal of Law & Policy, 2009)
The invention of the desktop computer and the widespread use of the Internet has revolutionized life in many ways over the last twenty-five years. It has also fundamentally changed the way in which we are able to study law. Since the 1980s, a vast amount of data has been collected about courts, both in the United States and abroad. We now have the requisite computing power to process and analyze these data, ultimately with the goal of learning how law works. Many law schools now house scholars who conduct empirical legal scholarship: scholarship that uses data and modern social scientific methods to understand law. At Washington University in St. Louis, the Center for Empirical Research in the Law provides infrastructure for this type of scholarship. Volume 29 of the Washington University Journal of Law and Policy contains eight excellent examples of this type of work conducted by scholars working in the legal academy, the social sciences, and their intersection. The articles focus broadly on decision-making in the federal courts. The authors use innovative data sources and state-of-the-art methodology to study all three levels of the federal judiciary. Three of the Articles in the volume look at decision-making in the federal district courts. The importance of ideology and the methodology used to detect it in the Federal Courts of Appeals is the focus of two articles in the volume. Finally, three articles look at the United States Supreme Court.
Keywords: Judicial process; Federal courts; Decision making; Empirical analysis; Research methodologies; U.S. Supreme Court